Analysis of implementation : the payroll accounting system and employee wages - Resca, Yuliana; Munandar, Agus (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The accounting system, especially the payroll accounting system, and employee wages will assist the company in managing the payment of wages and salary, thereby preventing fraud. Internal control will be influenced by a solid accounting system. The goal of this research is to determine the company's internal control effectiveness by examining how well payroll accounting information systems are applied. The research method used is a literature study. In the organizational structure, there is a lack of task separation and division. The authorization system and recording procedures and healthy practices have not been implemented properly. In conclusion, internal control aspects in the payroll and salary accounting systems have not been fully fulfilled in several companies.